2008
DOI: 10.1080/10401230802437365
|View full text |Cite
|
Sign up to set email alerts
|

Case Series: Sensory Intolerance as a Primary Symptom of Pediatric OCD

Abstract: Introduction Marked intolerance or intrusive re-experiencing of ordinary sensory stimuli that in turn drive functionally impairing compulsive behaviors are occasionally seen in young children with OCD. Methods We describe a number of children with DSM-IV OCD ascertained from a family genetic study of pediatric OCD, whose intolerance of ordinary sensory stimuli created significant subjective distress and time-consuming ritualistic behavior that was clinically impairing. Results In each case, these sensory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 23 publications
1
33
0
1
Order By: Relevance
“…At any rate, the proposed link between childhood oral and tactile hypersensitivity and adult OC symptoms is consistent with and may integrate several diverse findings. These include the increased disgust sensitivity (Shapira et al, 2003;Stein et al, 2001) and hypofunctioning in the sensory gating mechanism in OCD (Rossi et al, 2005), the association between childhood OCD and sensory sensitivity (Hazen et al, 2008), and the deficient sense of control in OCD (Obsessive Compulsive Cognitions Working Group, 2001;Sookman, Pinard, & Beck, 2001;Steketee, Frost, & Cohen, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At any rate, the proposed link between childhood oral and tactile hypersensitivity and adult OC symptoms is consistent with and may integrate several diverse findings. These include the increased disgust sensitivity (Shapira et al, 2003;Stein et al, 2001) and hypofunctioning in the sensory gating mechanism in OCD (Rossi et al, 2005), the association between childhood OCD and sensory sensitivity (Hazen et al, 2008), and the deficient sense of control in OCD (Obsessive Compulsive Cognitions Working Group, 2001;Sookman, Pinard, & Beck, 2001;Steketee, Frost, & Cohen, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…A potential link between sensory hypersensitivity and the use of excessive rituals has been suggested independently in research on ObsessiveeCompulsive Disorder (OCD) (Hazen et al, 2008;Shapira et al, 2003;Stein, Liu, Shapira, & Goodman, 2001) and in the discipline of occupational therapy (Baranek, Foster, & Berkson, 1997a,b). So far, no research has attempted to integrate these findings into a more comprehensive model.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, this information is largely based on anecdotal case reports, 20,21 studies using a broader definition of sensory problems 14 (e.g., including both over- and under-responsiveness), and research using unsystematically diagnosed or poorly characterized samples. In the Carter et al 3 and Van Hulle et al 15 studies, rates of specific psychiatric disorders were not reported, but the rate of diagnoses within the broad domains of internalizing disorders among those with SOR ranged from 10.0% 3 to 70.4% 15 and externalizing disorders from 18.5% 3 to 50.4%.…”
mentioning
confidence: 99%
“…Specifically, there is no information about how these children differ from typically developing children in the way they manage sensory information from inside and outside of their bodies. There is growing support, however, for differences in sensory processing in children with ADHD (Cheung & Siu, 2009;Dunn & Bennett, 2002;Hazen et al, 2008;Lane, Reynolds, & Thacker, 2010;Yochman, Parush, & Ornoy, 2004) and obsessive-compulsive symptoms (Dar, Kahn, & Carmeli, 2012;Hazen et al, 2008). The objective of this study was to determine whether sensory processing differences existed in children with TD compared to a normative sample.…”
Section: Introductionmentioning
confidence: 94%